Leading Educational Networks : Theory, Policy and Practice - Greany, Toby; Kamp, Annelies (London [England] : Bloomsbury Academic, 2022)
"This book offers a global perspective on educational networks, reviewing theory and practice before setting out four lenses: educational effectiveness and improvement; governance theory; complexity theory; and Actor-Network Theory. Using these lenses, Greany and Kamp explore the limits and possibilities for collaboration across Aotearoa New Zealand, Chile, England and Singapore. The four lenses allow the authors to explore the implications of networks from different perspectives: moving from the level of the individual school, to the local and national systems that schools operate within, to the wider environmental factors that shape, and are shaped by, network activity in education. The authors examine why and how networks have become a feature of education systems worldwide and the implications for policy, practice and research. They consider how networks form, develop, reform, and achieve impact, but also why they can be challenging and often fail to achieve their ambitions. The book concludes by drawing out the implications for leaders and the further development of leadership at different levels of education systems, and by identifying further avenues for research."--
Introduction -- 1. Understanding Networks in Contemporary Education Systems -- 2. Four Theoretical Lenses -- 3. Networks in England -- 4. Networks in Aotearoa, New Zealand -- 5. Analysing Networks Through the Lens of School Effectiveness and School Improvement -- 6. Analysing Networks Through the Lens of Governance Theory -- 7. Analysing Networks Through the Lens of Complexity Theory -- 8. Analysing Networks Through the Lens of Actor-Network Theory -- 9. The Theory and Practice of Network Leadership -- 10. Exploring the Implications of Networks for Policy and Practice -- Concluding Thoughts -- References -- Index.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Education -- Research; Education -- Information services; Information networks; Electronic books